Peran Mahasiswa KKN dalam Meningkatkan Semangat Mengaji Anak-Anak di Mushola Al Jihad Desa Talang Empat - Sally Rahma Putri; Meisya Hidayah; Yova Emelia Putri; Mia Pangedoan Siregar; Fasiman Loshabana; Kusmi Megawati; Restu Armada Siregar; Asep Syaifullah; Maslika Rahayu; Jella Velia Degsa (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This study explores the role of community service program (KKN) students in enhancing the enthusiasm of children in learning to recite the Qur’an at Mushola Al Jihad, Talang Empat Village. The issue addressed is the declining interest and motivation among children to attend Qur’anic learning sessions due to the lack of engaging teaching methods and limited support from local educators. The aim of this research is to identify and analyze the contributions made by KKN students in revitalizing the learning spirit among children through structured religious education activities. Using a qualitative approach, data were collected through observation, interviews, and documentation during the students’ community engagement period. The findings reveal that KKN students play a significant role in creating a more interactive and enjoyable learning environment, implementing creative teaching methods, and acting as motivators for children. Their presence also fosters greater parental involvement and community awareness regarding the importance of early religious education. The study concludes that student involvement in community-based religious education programs can effectively enhance children’s interest and participation in Qur’anic studies, thereby contributing to the broader goal of character development in rural communities.